2019
DOI: 10.1177/1729881419840213
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive fuzzy sliding mode controller for the depth control of an underactuated underwater vehicle

Abstract: An adaptive fuzzy sliding mode controller is proposed for the depth control of an underactuated underwater vehicle based on the state-dependent Riccati equation. An adaptive fuzzy control algorithm is embedded into the sliding mode controller to solve the buffering and mismatched uncertain problems in the robust sliding mode variable structure controller, where an auxiliary fuzzy control unit is designed to automatically adjust the scale factor of the main fuzzy controller output. Based on Lyapunov stability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The proposed adaptive fuzzy SMC (AFSMC) maintains the formation by coping with the variation in average velocity and lift forces. The FLC algorithm is combined with the SMC to compensate the buffering and chattering issues in the original SMC method (Chen et al, 2019). The required adaptive control law u v ðtÞ can be derived by employing "fixed control allocation scheme" and algebraic theory (Chen et al, 2017) as follows:…”
Section: Stability Analysis Of Afsmcmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed adaptive fuzzy SMC (AFSMC) maintains the formation by coping with the variation in average velocity and lift forces. The FLC algorithm is combined with the SMC to compensate the buffering and chattering issues in the original SMC method (Chen et al, 2019). The required adaptive control law u v ðtÞ can be derived by employing "fixed control allocation scheme" and algebraic theory (Chen et al, 2017) as follows:…”
Section: Stability Analysis Of Afsmcmentioning
confidence: 99%
“…According to the studies, fuzzy logic controllers can be classified as conventional, adaptive and hybrid (Xiang et al, 2018) based on the difference between the fuzzy rules and their generation methods. The application of AFSMC for diving control (Chu et al, 2018), trajectory tracking (Guerrero et al, 2019) and depth control (Chen et al, 2019) of underactuated AUV with input constraints has been found in the literature. In this research, an AFSMC has been proposed to cope with the case of actuator failure subjected to variation in payload mass due to the change in lift forces acting on an AUV surface (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the robustness to external disturbances, parameter perturbations, and unmodeled dynamics, SMC is an effective and powerful advanced controllers that have been developed considerably in USV and robot areas. [30][31][32][33][34][35] In practical applications, SMC has successfully applied to underactuated biped robot, 36 satellites, 37 and overhead crane. 38 For example, sliding mode observer was designed by Van et al 39 to estimate the robot velocities in the presence of model uncertainties and external disturbances.…”
Section: Introductionmentioning
confidence: 99%